Analysis of Students' Critical Thinking Skills in terms of Gender Using Science Teaching Materials Based on The 5E Learning Cycle Integrated with Local Wisdom (Jurnal Pendidikan IPA Indonesia, 2021)
Critical thinking is an important thing in building learners' knowledge. Students who have these skills will be able to solve problems effectively. This study examines the effect of science teaching materials based on the 5E learning cycle integrated with local wisdom in terms of gender on students' critical thinking skills. This quasi-experimental research with a pre-test-post-test control group design was carried out at Madrasah Tsanawiyah. Purposive sampling was used to select the research sample, including an experiment and a control group of equal ability between male and female students. The data were analyzed using a t-test and N-gain test to determine the improvement of critical thinking skills in both groups. The results showed that this teaching material affected students' critical thinking skills by the results of the t-test. The difference in the improvement of students' critical thinking skills is significant based on the result of N-gain and categorized as high. Students become more critical in solving problems after study using 5E integrated by local wisdom. The result shows an impact of this teaching material on first to fourth indicators of critical thinking skills. The fifth indicator is not affected by this teaching material because of students' weakness in elaborate the solution. There were also significant differences in the improvement of male and female students' critical thinking skills. One of them is that male students have a quicker response and higher self-confidence than female students in solving the problems. Based on this result, we conclude that applying science teaching material with 5E integrated by local wisdom positively affects students' critical thinking skills.